2015
DOI: 10.1016/j.celrep.2014.12.030
|View full text |Cite
|
Sign up to set email alerts
|

SART3-Dependent Accumulation of Incomplete Spliceosomal snRNPs in Cajal Bodies

Abstract: Cajal bodies (CBs) are evolutionarily conserved nuclear structures involved in the metabolism of spliceosomal small nuclear ribonucleoprotein particles (snRNPs). CBs are not present in all cell types, and the trigger for their formation is not yet known. Here, we depleted cells of factors required for the final steps of snRNP assembly and assayed for the presence of stalled intermediates in CBs. We show that depletion induces formation of CBs in cells that normally lack these nuclear compartments, suggesting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
77
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(83 citation statements)
references
References 64 publications
(98 reference statements)
6
77
0
Order By: Relevance
“…73 We recently showed that increased concentration of unassembled or defective snRNPs triggers formation of CBs in cells that are normally devoid of CBs. 37 This suggests that incomplete snRNPs enhance coilin self-interaction properties and induce formation of CBs through an unknown mechanism.…”
Section: Toward Cajal Body Formationmentioning
confidence: 99%
See 3 more Smart Citations
“…73 We recently showed that increased concentration of unassembled or defective snRNPs triggers formation of CBs in cells that are normally devoid of CBs. 37 This suggests that incomplete snRNPs enhance coilin self-interaction properties and induce formation of CBs through an unknown mechanism.…”
Section: Toward Cajal Body Formationmentioning
confidence: 99%
“…This finding suggests that coilin is part of a quality control mechanism that proofreads final snRNP assembly. 37 Again, this function might not be essential under normal conditions but becomes important when snRNP assembly is perturbed or when transcription and splicing rates are high, producing a large quantity of mono-snRNPs that require recycling and reassembly. Coilin-dependent concentration of mono-snRNPs in CBs would increase their assembly rate and at the same time prevent incomplete snRNPs from entering splicing reaction.…”
Section: Coilin Historymentioning
confidence: 99%
See 2 more Smart Citations
“…We have implemented this method, which we have named spectraFISH, for the study of 5 distinct genes or CTs with the CB, a major NB involved in spliceosomal snRNP biogenesis [31][32][33] and found frequently in cancer cells. 21 This nuclear structure actively coordinates 34 a network of gene pairing interactions with major and minor spliceosome U snRNA genes, [12][13][14]35 and other highly active intron-encoded U snoRNA/scaRNA genes, 21,36 but also histone gene clusters (e.g.…”
Section: Introductionmentioning
confidence: 99%